Discovery of thiosemicarbazone derivatives as effective New Delhi metallo-β-lactamase-1 (NDM-1) inhibitors against NDM-1 producing clinical isolates - Bing Zhao; Xinhui Zhang; Tingting Yu; Ying Liu; Xiaoling Zhang; Yongfang Yao; Xuejian Feng; Hongmin Liu; Dequan Yu; Liying Ma; Shangshang Qin (Elsevier, 2021)
New Delhi metallo-β-lactamase-1 (NDM-1) is capable of hydrolyzing nearly all β-lactam antibiotics, posing an emerging threat to public health. There are currently less effective treatment options for treating NDM-1 positive "superbug", and no promising NDM-1 inhibitors were used in clinical practice. In this study, structure-activity relationship based on thiosemicarbazone derivatives was systematically characterized and their potential activities combined with meropenem (MEM) were evaluated. Compounds 19bg and 19bh exhibited excellent activity against 10 NDM-positive isolate clinical isolates in reversing MEM resistance. Further studies demonstrated compounds 19bg and 19bh were uncompetitive NDM-1 inhibitors with Ki = 0.63 and 0.44 μmol/L, respectively. Molecular docking speculated that compounds 19bg and 19bh were most likely to bind in the allosteric pocket which would affect the catalytic effect of NDM-1 on the substrate meropenem. Toxicity evaluation experiment showed that no hemolysis activities even at concentrations of 1000 mg/mL against red blood cells. In vivo experimental results showed combination of MEM and compound 19bh was markedly effective in treating infections caused by NDM-1 positive strain and prolonging the survival time of sepsis mice. Our finding showed that compound 19bh might be a promising lead in developing new inhibitor to treat NDM-1 producing superbug.